HOW A TYPICAL CROWDFUNDING ROUND WORKS - Aminjon Kalandarov (Scholar Express Journals, 2023)
The article describes the typical process of a crowdfunding round and its relevant characteristics. Crowdfunding typically involves an exchange of services between the donor and the person seeking funds only if the target amount is reached within a specified timeframe. Backers in crowdfunding typically have no say in the implementation of the project and have to rely on their trust in the initiator. Crowdfunding also often involves offering unconventional services to sponsors that can have a more complex meaning than purely economic. The idea of swarm intelligence is also discussed, where a large number of donors participating in a financing project can indicate its success and create a momentum for others to participate. The article also touches on the role of donors as multipliers and the importance of ongoing media processing and transparency in financing through crowdfunding.
Keywords: Crowdfunding; Round; Legal Examination; Performance-related